Verbal interaction in the classroom at SMP Negeri 6 Majene: An analysis flanders interaction categories - Askiah Hasan; Putu Wahyu Sudewi (Journal of Research on English and Language Learning (J-REaLL), 2022)
The purpose of this study was to analyze the verbal interactions of students in class VIII of SMP Negeri 6 Majene, by analyzing the verbal interactions between teachers and students in class VIII of SMP Negeri 6 Majene in the 2020/2021 school year. This research is a descriptive qualitative research. Data collection techniques used checklist observation and video tapping. Researchers took 10 grade VIII students of SMP Negeri 6 Majene as research subjects. The results showed that in the teacher category more often appeared to accept feeling, ask question, criticizes / justifies authority. Furthermore, in the student category the most dominant was student talk response. In this case, researchers assess, that teachers and students are still lacking in verbal interaction and there are still many categories that have not been fulfilled. Furthermore, students also sometimes experience confusion and difficulty in proper verbal interaction. Then they don't really understand what is being discussed so they are afraid of being wrong even though students know what to say to the teacher.